(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Reforming our country’s agriculture, especially improving the state management system in the sector, wide introduction of market relations, strengthening the legal basis of relations between entities that grow, process and sell agricultural products, attract investments to the sector, introduce resource-efficient technologies, and encourage producers of agricultural products Certain works are being carried out to provide modern equipment. In the article, diversification of production, improvement of land and water relations, creation of a favorable agribusiness environment and high added value chain, support for the development of cooperative relations, wide introduction of market mechanisms, information and communication technologies in the field, as well as effective use of scientific achievements are discussed in the article. issues are focused on.